Cancer symptom cluster research in pediatric oncology: a work in progress - Luciana Chain Veronez; Luís Carlos Lopes-Júnior (Open Exploration Publishing Inc., 2024)
In the 21st century, advances in basic research have provided new insights in the field of pediatric oncology. Pediatric patients tend to experience higher levels of distressing symptoms, which together form a symptom cluster. In clinical practice, these symptom clusters are reported daily by children and adolescents with cancer. Translational research has emerged as the translation of new knowledge from basic science into clinical practice. Understanding how neuroimmunoendocrine pathways regulate cancer development and the aspects underlying the specific therapies, such as chemotherapy and immunotherapy, is an important frontier for future research in pediatric oncology. The goal of translational research is to show how different variables in tumor and patient characteristics explain the differential effects of interventions, as translational research provides new insights into the management of cancer symptoms in children and adolescents with cancer. Together, this approach could lead to improvements in pediatric oncology care worldwide.